Characterization of wet aggregate stability of soils by H‐NMR relaxometry. (10th October 2014) - Buchmann, C.; Meyer, M.; Schaumann, G. E.; Simpson, Andre J.
<x xml:space="preserve">Abstract</x> For the assessment of soil structural stability against hydraulic stress, wet sieving or constant head permeability tests are typically used but rather limited in their intrinsic information value. The multiple applications of several tests is the only possibility to assess important processes and mechanisms during soil aggregate breakdown, e.g. the influences of soil fragment release or differential swelling on the porous systems of soils or soil aggregate columns. Consequently, the development of new techniques for a faster and more detailed wet aggregate stability assessment is required. 1H nuclear magnetic resonance relaxometry (1H‐NMR relaxometry) might provide these requirements because it has already been successfully applied on soils. We evaluated the potential of 1H‐NMR relaxometry for the assessment of wet aggregate stability of soils, with more detailed information on occurring mechanisms at the same time. Therefore, we conducted single wet sieving and constant head permeability tests on untreated and 1% polyacrylic acid‐treated soil aggregates of different textures and organic matter contents, subsequently measured by 1H‐NMR relaxometry after percolation. The stability of the soil aggregates were mainly depending on their organic matter contents and the type of aggregate stabilization, whereby additional effects of clay swelling on the measured wet aggregate stability were identified by the transverse relaxation time (T2) distributions. Regression analyses showed that only the percentage of water stable aggregates could be determined accurately from percolated soil aggregate columns by 1H‐NMR relaxometry measurements. 1H‐NMR relaxometry seems a promising technique for wet aggregate stability measurements but should be further developed for nonpercolated aggregate columns and real soil samples. Copyright © 2014 John Wiley & Sons, Ltd.